Neoadjuvant Therapy With Cabozantinib as a Bridge to Liver Transplantation in Patients With Hepatocellular Carcinoma (HCC): A Case Report - Bhardwaj, Hiral; Fritze, Danielle; Mais, Daniel; Kadaba, Venkatesh; Arora, Sukeshi Patel (Frontiers in Transplantation, 2022)
Liver transplant (LT) is the treatment of choice for unresectable, localized hepatocellular carcinoma (HCC). However, transplant is not recommended for patients who have extensive tumor growth and do not meet specific criteria. For these cases, “bridging” therapies are often used to either downstage or prevent tumor progression while patients are on the transplant list. Various pre-transplant therapies have been used, including transarterial chemoembolization, radiofrequency ablation, and systemic therapies. Sorafenib is a well-known systemic agent used for HCC, but research is limited on its use as well as the use of newer agents as bridging therapy. Prospective studies are also lacking. We discuss cases of two patients diagnosed with HCC and treated systemically with cabozantinib prior to transplant without treatment-related complications. This suggests that cabozantinib could be safely used after sorafenib therapy to control disease related to HCC while awaiting liver transplantation.